Special Issue Dedicated to the Memory of Elsa Beatriz Abuin Saccomano (1942–2012). (4th November 2013) - Alarcon, Emilio Isaac; Aspee, Alexis; Aliaga, Carolina; Braslavsky, Silvia E.
Abstract : In memoriam of Elsa Abuin (1942–2012), teacher, mentor and friend. This Special Issue presents a collection of review articles and papers dedicated to the memory of Elsa Abuin and most of them presented during the Meeting of the Latin‐American photochemists (Encuentro Latino‐Americano de Fotoquímica y Fotobiología, ELAFOT) held in October 2012 in Córdoba, Argentina.